2023
DOI: 10.1021/acsnano.3c00388
|View full text |Cite
|
Sign up to set email alerts
|

Local Temperature Increments and Induced Cell Death in Intracellular Magnetic Hyperthermia

Abstract: The generation of temperature gradients on nanoparticles heated externally by a magnetic field is crucially important in magnetic hyperthermia therapy. But the intrinsic low heating power of magnetic nanoparticles, at the conditions allowed for human use, is a limitation that restricts the general implementation of the technique. A promising alternative is local intracellular hyperthermia, whereby cell death (by apoptosis, necroptosis, or other mechanisms) is attained by small amounts of heat generated at ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…Thus, a deeper understanding of the heat transfer inside the nHs might provide information for future alternate designs ( e.g ., enzymes with different optimal T , MNPs with different heating capacities, and thermally responsive Si). Indeed, advancements in measuring the temperature of the nanoheater currently follow two strategies: (i) utilizing a second nanoparticle for thermometry (known as the dual-particle approach) and (ii) attaching a molecular thermometric probe to the surface or outer shell of the nanoheater (known as the single-particle approach). , However, the use of any of those methods implies the modification of the nH surface or the addition of a new component into the silica matrix. This may result in a different hierarchical integration of the components that may alter the nH properties, especially the efficiency of the remote activation of the HRP.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a deeper understanding of the heat transfer inside the nHs might provide information for future alternate designs ( e.g ., enzymes with different optimal T , MNPs with different heating capacities, and thermally responsive Si). Indeed, advancements in measuring the temperature of the nanoheater currently follow two strategies: (i) utilizing a second nanoparticle for thermometry (known as the dual-particle approach) and (ii) attaching a molecular thermometric probe to the surface or outer shell of the nanoheater (known as the single-particle approach). , However, the use of any of those methods implies the modification of the nH surface or the addition of a new component into the silica matrix. This may result in a different hierarchical integration of the components that may alter the nH properties, especially the efficiency of the remote activation of the HRP.…”
Section: Resultsmentioning
confidence: 99%
“…In their Comment, Maldonado and Goya, while acknowledging the elegance of the method we presented in ref , argue that the variation in the local temperature of γ-Fe 2 O 3 magnetic nanoheaters during magnetic hyperthermia experiments, as measured using a Sm 3+ /Eu 3+ ratiometric luminescent thermometer located on the surface, is the global temperature of the cell. Consequently, they suggest that there is no significant local temperature gradient between the nanoheater and its surrounding environment.…”
mentioning
confidence: 94%
“…In their recent publication, Gu et al reported on the variation of local temperature produced by magnetic nanoparticles (MNPs) under alternate magnetic fields (AMF), as measured by a radiometric luminescent nanothermometer. MNPs’ capacity to generate nanoscale hot spots under AMF has been contested since Gordon et al’s 1979 intracellular hyperthermia hypothesis .…”
mentioning
confidence: 99%
“…Nevertheless, the enduring discussions on the actual existence of nanoscale thermal focal points persist due to the lack of unequivocal experimental substantiation, as no direct technique to measure temperature at the submicrometer scale and intracellular space was available. For this reason, the article of Gu et al attracted our attention, since it reports on an effective and elegant solution to assess the local temperature increase through a direct luminescent probe on the MNPs surface that changes with temperature. However, in contrast to the inferences made by the authors, we posit that this study gives a corroboration for the lack of localized thermal effects in magnetic hyperthermia experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation